GENOTOXIC AND CYTOTOXIC EFFECTS IN HOST CELLS AT TAENIIDOSIS - V. Ya. Bekish; V. V. Zorina (Российский паразитологический журнал, 2016)
Objective of research:  The pork and beef tapeworm infestation is characterized by the  increase of single-strand breaks,  alkali-labile sites in nuclear DNA of bone marrow cells of golden hamsters. A triple subdermal sensibilisation with protein somatic products from the  tissue of Taenia solium or Taeniarinchus saginatus is accompanied by a genotoxic effect in somatic bone marrow cells and generative cells in mouse seminal vesicles. It is manifested by increased single-strand breaks and alkali-labile sites in a nuclear DNA. The increase of damage of nuclear DNA depends on the dose of protein somatic products from the tissue of T. saginatus, it authentically grows up when a higher dose is used. Protein somatic products from the tissue of T. solium  or  T. saginatus  at  subdermal sensibilisation have  a cytotoxic effect manifested  in growth  of apoptotic cells in bone marrow and seminal vesicles. Materials and methods.  To study the genotoxic and cytotoxic effects in genome of mammals at taenia  infection and at  triple subdermal  sensibilisation with protein somatic products from the tissue of T. solium or T. saginatus the alkaline single cell gel electrophoresis by Singh et al., modified by  Hellman et al. (comet) assay is used for investigation of  bone marrow and seminal vesicles. Results and discussion. The values of the alkaline single cell gel electrophoresis (comet)  assay of bone marrow and seminal vesicles at T. solium or T. saginatus infection in golden hamsters were determined on 45th day of infestation.